The emergence of the physical culture and sports movement in Ukraine in the late 19th and early 20th centuries - Saltan , Nataliia; Saltan , Oleksandr; Olkhovyi , Oleh (Sportyvnyi Visnyk Prydniprovia, 2026)
Introduction. For over a century, physical culture has reflected changes in society. It has come a long way in development. Previously, it was only gymnastic holidays and individual competitions. Today, it is a large-scale system of mass sports, sports of higher achievements and recreation. The purpose of the study to determine the geography and main participants of the sports movement. The work analyzes the organizational forms and areas of activity of the societies of that time. The study aims to establish the number of such organizations and propose their classification. Research material and methods. The work used an analysis of scientific literature, the press of the early 20th century and regulatory documents. The comparative-historical research method was also applied. Results. The article reveals the process of the emergence of the first sports organizations. Initially, they arose as an initiative of the citizens themselves. Over time, these associations became part of the state management system. Sports developed due to the activity of society. Only later did it begin to be consistent with government policy. Foreigners played a large role in this process. It was they who spread British ideas about athleticism and competitions. This contributed to the popularity of modern sports in Ukrainian lands. At that time, there were no clear rules and a unified management system. Because of this, official clubs existed alongside numerous amateur clubs. There were especially many such associations in football. This was a characteristic feature of the initial stage of the development of sports. Sports societies had very diverse tasks. They not only conducted training. Activists built playgrounds and halls for classes. They also created places for recreation and educated young people. Representatives of different social groups participated in the movement. Women and children actively participated in sports. This indicates the openness of the movement to all segments of the population. Physical culture and sports movement was a widespread phenomenon In the Western Ukrainian lands. Its scale was comparable to that of European countries. Within the Russian Empire, it was less common, especially in villages. The author proposes to divide societies into three groups: socio-educational, gymnastic and specialized. Conclusions. The sports movement was formed as a public initiative. Later, the state joined this process. The development was influenced by foreign traditions and the multidisciplinary nature of organizations.